2022
DOI: 10.3389/fonc.2022.989483
|View full text |Cite
|
Sign up to set email alerts
|

The genetics of myelodysplastic syndromes and the opportunities for tailored treatments

Abstract: Genomic instability, microenvironmental aberrations, and somatic mutations contribute to the phenotype of myelodysplastic syndrome and the risk for transformation to AML. Genes involved in RNA splicing, DNA methylation, histone modification, the cohesin complex, transcription, DNA damage response pathway, signal transduction and other pathways constitute recurrent mutational targets in MDS. RNA-splicing and DNA methylation mutations seem to occur early and are reported as driver mutations in over 50% of MDS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 266 publications
1
11
1
Order By: Relevance
“…37 SETBP1 somatic mutations mainly involve 858-874 residues and could co-occur with À7/del(7q) abnormalities or with inv(16q10) (41%-54% of cases); however, their frequency in low-risk MDS is low, accounting for 2%-5% of cases, even though their presence conferees a poor prognosis. 31,43,44 In our study, SETBP1 variants, both pathogenic and VUS, were found in more than 50% of AML and MDS subjects, mostly localized between the AT hook 2 and the SET-binding domain. Moreover, MDS patients showed a higher genetic complexity compared to CCUS, as MDS subjects more frequently had two or more SETBP1 variants, especially…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…37 SETBP1 somatic mutations mainly involve 858-874 residues and could co-occur with À7/del(7q) abnormalities or with inv(16q10) (41%-54% of cases); however, their frequency in low-risk MDS is low, accounting for 2%-5% of cases, even though their presence conferees a poor prognosis. 31,43,44 In our study, SETBP1 variants, both pathogenic and VUS, were found in more than 50% of AML and MDS subjects, mostly localized between the AT hook 2 and the SET-binding domain. Moreover, MDS patients showed a higher genetic complexity compared to CCUS, as MDS subjects more frequently had two or more SETBP1 variants, especially…”
Section: Discussionsupporting
confidence: 48%
“…29,30 In MDS, genetic landscape differs between low-and high-risk MDS and between those myelodysplasias that rapidly progress to AML. 29,31,32 Accumulation of epigenetic modifications together with occurrence of TET2, IDH1, and IDH2 gene mutations are proposed as the main driven genetic events favoring MDS transformation to AML. 7,29,33 Most frequent mutations involve SF3B1, TET2, ASXL1, SRSF2, DNMT3A, RUNX1, U2AF1, ZRSR2, STAG2, TP53, EZH2, CBL, JAK2, BCOR, IDH2, NRAS, and NF1 genes, and some of these alterations have prognostic impact, such as SF3B1 mutations associated with the presence of ring sideroblasts and altering spliceosome machinery activities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations